P39 'We're meat, so we need to eat meat to be who we are': understanding motivations that increase or reduce meat consumption among emerging adults in the University of Ghana food environment. (26th August 2022) - Mensah, Daniel; Mintah, Faustina Ofosua; Oteng, Sylvia Adoma; Lillywhite, Rob; Oyebode, Oyinlola
Abstract : Background: The increasing presence of meat and other ASFs in the diets of sub-Saharan African (SSA) populations have consequences for human and planetary health in the subregion. Dietary modifications that favour healthy and sustainable, largely plant-based diets will offer dual health and environmental benefits. But are emerging adults in the Ghana (or the SSA setting) who are both important targets and potentially key drivers of dietary change willing to modify their diets or dietary behaviours for health and ecological benefits? Methods: This qualitative study explored motivations and willingness of emerging adult university students to adopt healthy and sustainable diets. The study used focus group discussions in combination with interviews with best friend dyads. Verbatim transcripts were analysed thematically using NVivo 12. Results: Eight themes highlighted various motivations to increase or reduce meat consumption, some of which participants deemed more relevant than others. Health concerns; animal welfare; and environmental sustainability were not important to this age group, and they did not consider changing their behaviour on the basis of these drivers. Body weight and shape; meat as identity, pleasure, and joy; meat eating as part of socialization were important drivers of increased meat consumption; religion and cultural practices were important drivers of limited meat consumption. Students viewed emerging adulthood as the best period to enjoy meat. The study finds body image and weight concerns to be both drivers of increased preference for more meat (more dominant) and conversely, a motive for intentions to reduce meat consumption. Climate change was not an important driver of behaviour, likely due to limited awareness of climate change. However, upon explanation, environmental sustainability seemed to have potential as an issue that interested these emerging adults and could motivate them to reduce meat consumption. Animal welfare was also a new concept to participants. Even when explained, unlike the concept of environmental sustainability, this student sample was not persuaded to modify their meat consumption based on animal welfare. However, substituting portions of their meat with plant protein appeared to appeal to this student sample. Conclusion: Given the complexity of factors driving meat-eating behaviour in these emerging adults and the deep-seated role meat plays in the diets of the cultures represented in this study, a multi-level and multidisciplinary approach may be required to shift diets towards sustainable and healthy plant-based diets. However, this may take time.